Examination of factors explaining coaching strategy and training methodology as correlates of potential doping behavior in high-level swimming - Liposek, S.; Zenic, N.; Saavedra, J. M.; Sekulic, D.; Rodek, J.; Marinsek, M.; Sajber, D. (Journal of Sports Science & Medicine, 2018)
Although coaching is considered an important determinant of athletes` potential doping behavior (PDB), there is an evident lack of studies that have examined coaching-strategy-and-training-methodology (CS&TM) in relation to PDB. This study was aimed to identify the specific associations that may exist between CS&TM -factors and other factors, and PDB in high-level swimming. The sample comprised 94 swimmers (35 females; 19.7 ± 2.3 years of age) and consisted of swimmers older than 18 years who participated in the 2017 National Championship. Variables were collected by previously validated questionnaires, with the addition of questions where athletes were asked about CS&TM to which they had been exposed. Multinomial logistic regression was applied for the criterion PDB (Negative PDB - Neutral PDB - Positive PDB). The higher risk for positive-PDB was found in males (OR: 6.58; 95%CI: 1.01-9.12); therefore, all regressions were adjusted for gender. Those swimmers who achieved better competitive result were less prone to neutral-PDB (0.41; 0.17-0.98). The positive-PDB was evidenced in those swimmers who perceived that their training was monotonous and lacked diversity (1.82; 1.41-5.11), and who were involved in training which was mostly oriented toward volume (1.76; 1.11-7.12). The lower likelihood of positive-PDB is found in those who replied that technique is practiced frequently (0.12; 0.01-0.81), those who replied that coach regularly provided the attention to explain the training aims (0.21; 0.04-0.81), and that coach frequently reviewed and discussed the quality of execution of specific tasks (0.41; 0.02-0.81). The findings on the relationships between the studied variables and PDB should be incorporated into targeted anti-doping efforts in swimming. Further studies examining sport-specific variables of CS&TM in younger swimmers and other sports are warranted.